Implementasi Sistem Informasi Manajemen Terintegrasi Berbasis Web untuk Rekrutmen dan Alokasi Tenaga Relawan Bencana Provinsi Lampung - Wulandari, Eka; Nursiyanto, Nursiyanto; Wasilah, Wasilah; Saleh, Sushanty (JURNAL PETISI (Pendidikan Teknologi Informasi), 2025)
Indonesia is one of the countries highly prone to natural disasters, thus requiring an effective and fast disaster management system. Volunteers play a crucial role in disaster management activities. However, in Lampung Province, the recruitment and allocation processes for volunteers still face several challenges, such as manual data recording, decentralized information, and difficulties in distributing volunteers to affected areas. This research aims to implement an integrated web-based management information system to support more efficient and structured recruitment and allocation processes. The system development method used is the Waterfall model, consisting of requirement analysis, system design, implementation, testing, deployment, and maintenance stages. Data collection was conducted through literature studies, observation, interviews, and documentation. The system was developed using PHP, HTML, CSS, JavaScript, and MySQL, and was tested using black-box testing to ensure it meets user requirements. The result of this study is a web-based application that accelerates volunteer recruitment, enables real-time data updating, and optimizes the allocation of volunteers to disaster-affected areas. It is expected that this system will improve the efficiency and effectiveness of disaster volunteer management in Lampung Province and can serve as a model for other regions with similar conditions.